MiR-199-3p Suppressed Inflammatory Response by Targeting MECP2 to Alleviate RTX-Induced PHN in Mice. (July 2022) - Wang, Zhijian; Shen, Wei; Zhu, Mengye; Xu, Mu; Qiu, Mizhen; Zhang, Daying; Chen, Shibiao
Varicella zoster virus–induced postherpetic neuralgia (PHN) can be alleviated by limited medications with serious side effects. This study aims to investigate the underlying molecular mechanism of miR-199-3p in mediating PHN in mice. 293T cells were transfected with miR-199-3p vectors (mimic/inhibitor). The target relationship between miR-199-3p and MECP2 was confirmed using luciferase reporter assay. PHN mouse model was established by RTX injection. Animal behaviors were evaluated using Hargreaves test and Von Frey test. Western blot was used for protein analysis, and quantitative reverse transcription polymerase chain reaction was performed for messenger RNA quantification. Serum levels of inflammatory mediators were determined using ELISA. Increased thermal withdrawal latency (TWL) and decreased mechanical withdrawal threshold (MWT) were observed in resiniferatoxin-induced PHN mice. Downregulated miR-199-3p and upregulated MECP2 were found in PHN mice. Upregulated miR-199-3p increased PWL and MWT, but inhibited MECP2 in PHN mice. Besides, increased miR-199-3p suppressed proinflammatory indicators and activated anti-inflammatory mediators. It also found that MECP2 was the target of miR-199-3p. Further study showed miR-199-3p enhanced PWL and MWT, and supported inflammatory response via targeting MECP2. miR-199-3p regulated inflammation by targeting MECP2 to alleviate RTX-induced PHN in mice.